Fabrication and Characterization of GaN-Based Fin-Channel Array Metal-Oxide-Semiconductor High-Electron Mobility Transistors With Recessed-Gate and Ga₂O₃ Gate Insulator Layer - Hsin-Ying Lee (IEEE, 2021)
In this work, the properties of gallium oxide (Ga2O3) and its excellent interface properties to GaN-based materials are explored as a gate insulator layer for GaN-based metal-oxide-semiconductor high-electron mobility transistors (MOSHEMTs). A novel vapor cooling condensation system was used to deposit the high quality Ga2O3 films with high insulation and low defect suitable for gate insulator layer. The characteristics of the Ga2O3 films were further explored by implementing GaN-based fin-channel array MOSHEMTs with recessed-gates and different channel widths. Compared to planar channel structure, the direct current, high frequency, and flicker noise performances were enhanced in the fin-channel MOSHEMTs with Ga2O3 gate insulator layer. For the GaN-based fin-channel array MOSHEMTs with 300-nm-wide channel, the devices exhibited superior performances of maximum extrinsic transconductance of 194.2 mS/mm, threshold voltage of −1.4 V, extrinsic unit gain cutoff frequency of 6.4 GHz, maximum oscillation frequency of 14.8 GHz, and normalized noise power of 8.45 $× \,\, 10^{-15}$ Hz $^{-1}$ . It was also demonstrated that the associated performances were improved by reducing the width of fin-channel array.